Engaging Dwight Radcliff’s Remixing the Center - Aycock, Jennifer L. (Missiology, 2025)
In this response, the author engages Dwight Radcliff’s contributions in Remixing the Center by demonstrating the pastoral and historiographical possibilities that emerge through use of Hip Hop Culture’s practices of sampling, mixing, and poesis. The author expands on Radcliff’s notion of pericolonial by suggesting some hopeful and pessimistic interpretations of youth dis-engagement, or sideways engagement, from institutional religious life. In conclusion, the author points to the globalization of HHC as indicating the potential of applying Radcliff’s missiological intervention at global scales of analysis and practice.